2011
DOI: 10.1159/000322886
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemia: A Possible Link between Insulin Resistance, Metabolic Dyslipidemia, and Heart and Kidney Disease (the Cardiorenal Syndrome)

Abstract: Resistance to insulin metabolic signaling in adipose tissue contributes to the lipid abnormalities in obese, hyperinsulinemic, insulin-resistant patients who develop the cardiorenal syndrome. These same metabolic dyslipidemic abnormalities can be found in conditions of caloric energy restriction with decreased adiposity or normal insulin levels, such as anorexia, starvation or non-diabetic kidney disease. In this review, we assess hypoglycemia as an alternative physiological explanation for the biochemical and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 102 publications
1
9
0
1
Order By: Relevance
“…Therefore, hyperinsulinemia and insulin resistance do not necessarily have to be responsible for the occurrence of hypoglycemia. However, there are studies with HR patients who had insulin resistance and significant impairment of insulin secretion [ 31 , 32 ]. Due to discrepancies in the findings of the studies and considering the lack of up-to-date evidence from other publications, further research focusing on insulin secretion and insulin sensitivity in RH patients is required.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, hyperinsulinemia and insulin resistance do not necessarily have to be responsible for the occurrence of hypoglycemia. However, there are studies with HR patients who had insulin resistance and significant impairment of insulin secretion [ 31 , 32 ]. Due to discrepancies in the findings of the studies and considering the lack of up-to-date evidence from other publications, further research focusing on insulin secretion and insulin sensitivity in RH patients is required.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, more sensitive markers of pre-clinical glucose dysregulation (FI, HOMA 2 ) were positively associated with depression at age 18 years. IR in combination with low FPG shows biological plausibility; FPG can present low-normal in early IR, in response to the IR phenotype of increased insulin secretion thus increased intracellular glucose uptake (Ensling et al ., 2011). These associations were not significant following demographic and lifestyle adjustments suggesting that the metabolic dysfunction present in depression may be attributable to sociodemographic and lifestyle factors.…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact mechanism is not well understood, a preclinical study demonstrated that hypoglycemia can induce nonesterified fatty acid elevation in adipose tissue, which is subsequently associated with kidney damage. 35 In addition, hypoglycemia could induce sympathetic surges, altering renal hemodynamics 10 ; acute fluctuations in blood glucose levels also trigger oxidative stress, which may be responsible for renal function impairment. 9 …”
Section: Discussionmentioning
confidence: 99%